Un passé national pour le « bolsonarismo » : les usages politiques de l'indépendance dans le Brésil contemporain - Fernando Nicolazzi (IdeAs)
In this article, I analyze the uses of the past in contemporary Brazil, taking as a case study how the history of Brazilian independence (1822) is manipulated by extreme right sectors that configure the political ideology of "bolsonarismo". One of these sectors is represented here by Brasil Paralelo, an audiovisual producer company that acts in the context of the so-called "culture wars" in Brazilian society. I argue that this way of using the past functions as a political mythology that seeks to manipulate and moralize history.